PELATIHAN SISTEM INFORMASI REKAM MEDIS DI PUSKESMAS PEMBANTU PEJUKUTAN, NUSA PENIDA BALI - nyoman purnama; A. A. Istri Ita Paramitha (DHARMA RAFLESIA, 2020)
Pejukutan village is one of the villages in Nusa Penida sub-district, Klungkung regency, Bali province. In the health sector in this village there is a Helper Health Center. Pejukutan Supporting Health Center is one of the agencies engaged in the field of public health that helps Puskesmas I Nusa Penida. The Pejukutan Supporting Health Center has only one health worker (nurse) in handling all health services located in the village of Pejukutan Nusa Penida District, Klungkung Regency. The service system of the Public Health Center of Pejukutan is still using a conventional system, namely the processing of patient medical record data which still uses bookkeeping or manual media which is then recapitulated by health workers to make medical reports. In addition the outpatient service process is often hampered because the process of searching outpatient medical records data by manual is quite long. To overcome this, an electronic-based medical record system was developed. This information system is made with a code ignitter framework. To run it requires a web browser like Mozilla or chrome. The realization of the application of the medical record information system at the Pejukutan health center, Pejukutan village, Nusa Penida, Klungkung Bali has been successfully carried out. This medical record system is felt to be more effective and efficient by officers when compared to the old reporting method.